2014
DOI: 10.1038/cddis.2014.464
|View full text |Cite
|
Sign up to set email alerts
|

CDK1 plays an important role in the maintenance of pluripotency and genomic stability in human pluripotent stem cells

Abstract: Human embryonic stem cells (hESC) and induced pluripotent stem cells (hiPSC) are characterised by an unusual and tightly regulated cell cycle that has been shown to be important for the maintenance of a pluripotent phenotype. Cyclin-dependant kinase 1 (CDK1) is a key player in cell cycle regulation and particularly mitosis; however, its role has not been studied previously in hESC and hiPSC. To investigate the impacts of CDK1 downregulation, we performed RNA interference studies which in addition to expected m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 54 publications
3
71
0
Order By: Relevance
“…Loss of CDK1 in human ES cells results in a reduction of pluripotency gene expression, including the core factors OCT4, KLF4, and LIN28, and subsequently increases differentiation [33]. Additionally, these cells show increased DNA damage and ensuing apoptosis [33,34]. Similar results were found performing chemical CDK2-inhibition in human ES cells [35].…”
Section: Reciprocal Regulation Of Cell Cycle and Pluripotency Networkmentioning
confidence: 85%
See 1 more Smart Citation
“…Loss of CDK1 in human ES cells results in a reduction of pluripotency gene expression, including the core factors OCT4, KLF4, and LIN28, and subsequently increases differentiation [33]. Additionally, these cells show increased DNA damage and ensuing apoptosis [33,34]. Similar results were found performing chemical CDK2-inhibition in human ES cells [35].…”
Section: Reciprocal Regulation Of Cell Cycle and Pluripotency Networkmentioning
confidence: 85%
“…Indeed there are several examples of how the high CDK activity in ES cells may influence the pluripotency network. Loss of CDK1 in human ES cells results in a reduction of pluripotency gene expression, including the core factors OCT4, KLF4, and LIN28, and subsequently increases differentiation [33]. Additionally, these cells show increased DNA damage and ensuing apoptosis [33,34].…”
Section: Reciprocal Regulation Of Cell Cycle and Pluripotency Networkmentioning
confidence: 99%
“…3 Cdk1 is also essential for meiosis in mouse oocytes, 4 and the suppression of Cdk1 leads to the differentiation of mouse trophoblast stem cells into giant cells. 5 Recently, it has been demonstrated that Cdk1/CDK1 is required for self-renewal in both mESCs and human embryonic stem cells (hESCs), 6, 7 which might be related to its interaction with Oct4. 8, 9 CDK1/CDK2 potentially regulates a large number of substrates (at least 1220) during hESC differentiation.…”
mentioning
confidence: 99%
“…Cyclin D1, cyclin B and cdc2 (CDK1) are involved in cell cycle regulation during G1 and G2/M phases [37] and have been reported to help regulate pluripotency in human embryonic/induced pluripotent stem cells [38] and were down-regulated in SSCs on SQ. Negative regulators of the cell cycle, p21 Cip1 , p19INK4D and p18INK4C ), were also down-regulated on SQ, which suggests that cell cycle progression is occurring on this surface ( i.e.…”
Section: Discussionmentioning
confidence: 99%